Scope of surgery for intracranial aneurysm in the elderly: a preliminary report. Issue 6132 (22nd July 1978) - Sengupta, R P; Lassman, L P; Hankinson, J
Abstract : Thirty-two elderly patients were reviewed six months to six years after intracranial surgery for subarachnoid haemorrhage. Out of 24 patients whose surgical outcome had been satisfactory, one had died from an unrelated illness and the remainder were well and leading normal lives. Eight patients had a poor outcome, which in some cases was due to factors other than age. In only three could a poor outcome be attributed to early surgery and advanced age. The results confirm that in at least three-quarters of patients aged 60-65 the risk of further haemorrhage can be removed by surgery without causing a major neurological deficit.